Disaster preparedness of professional nurses in a central urban public sector tertiary hospital in Johannesburg - Vaughan, Craig (My University, 2019)
Background: Large scale disasters globally demonstrate that no one person nor country is immune from the threat of natural disasters or other tragedies. Although South Africa has been relatively free from large scale disasters, this does not override the need for a responsible society for disaster preparedness. According to Garbutt, Peltier and Fitzpatrick (2008), research is needed to assess nurses’ familiarity with disaster preparedness as it is crucial to have a nursing workforce that would be prepared and willing to respond. Aim: The aim of this study was to explore and describe disaster preparedness of professional nurses in a central urban public sector tertiary hospital in Johannesburg, with the intention of making recommendations for clinical practice and education of such nurses. Setting: The setting for the study was the Emergency Departments and Intensive Care Units at a public sector tertiary hospital in Johannesburg. Design and Methods: A quantitative, explorative, descriptive and cross sectional research design was utilised in this study. The total population for this study was 210 (N = 210). Eighty (n=80) respondents returned their completed questionnaires, which gave a 38.09% response rate. Data was collected using an adapted survey questionnaire developed by Fung, Loke and Lai (2008). Results: The majority of nurses (92.5%; n = 74) in this study indicated they were not adequately prepared for disasters, while only 6.3% (n = 5) acknowledged they felt fully prepared. The nurses believed they could contribute to disaster preparedness through their roles as educators (73.8%; n = 59), coordinators (71.3%; n = 57) and caregivers (70.0%; n = 56). Most of the respondents were aware of existing protocols of disaster management at the hospital, but only 2.5% had read them. Courses taken in such areas as basic first aid (50.0%; n = 40), trauma life support (42.5%; n = 34) and disaster management (41.3%; n = 33) were cited as important in preparing for disasters. Conclusion: Nurses in this study revealed they were not sufficiently prepared for disasters, nor had they read the disaster management protocols. Recommendations are made for clinical practice and education of professional nurses.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2019